UTAUT’S performance consistency: Empirical evidence from a library management system - Zainab, A.M.; Kiran, K; Karim, N.H.A; Sukmawati, M. (Malaysian Journal of Library and Information Science, 2018)
This paper aims to investigate the use of an adapted UTAUT model to explore librarians’ acceptance of Radio-frequency Identification based Library Management System (RFID-LMS) and to determine the performance consistency of UTAUT when applied in a context other than its original intent. Causal relationships between the five identified constructs and their significances are determined using multiple regression method. The results are then compared to the performance of UTAUT as reported in the originating article. The relationship between external variables, attitude and selfefficacy, along with UTAUT constructs and RFID-LMS acceptance were found to be significant. The reliability of the modified UTAUT was found to be consistent with the original UTAUT. These findings have implications on the theoretical foundations of UTAUT and supports the notion of a unified view of examining technology adoption and diffusion.